Unicorns and Business Incubators in the Indian Startup and SME Ecosystem : A Quantitative Analysis - Sakthivel, Adithya Vikram (AMC Indian Journal of Entrepreneurship, 2021)
This paper investigated the Indian unicorn (startups or privately owned companies which are worth over a billion US dollars) ecosystem of the last decade and the possible effects that business incubators located in the country might have in the nurturing and development of such startups. This paper provides a quantitative analysis based on the thirty-six unicorn startups coming out of India in the decade between 2011 and 2020 to support its findings on the noticeable effects of business incubators on unicorns, and whether these incubators truly do play a major role in the growth cycles of the said unicorn startups in India.